(untitled) (Nigerian Journal of Technology, 2020)
Piston is an important internal combustion engine component that works with other engine components to withstand severe stresses and high temperature that are generated in the combustion chambers. Pistons are subjected to a very high mechanical and thermal load which results from extreme pressure cycles and huge forces of inertia caused by extremely high acceleration during the reciprocating motion. The 0.67hp generator piston designed had the values of parameters to be: 51.00mm Piston stroke; 48.85mm piston bore diameter; 3.66kw brake power; 4.87kw indicated power; 11.63Nm engine torque; 3.22mm piston thickness and 9.44cm3 clearance volume. The piston parameter values calculated were found to be in accordance with the recommended range of values in the design and operating data for internal combustion engines. http://dx.doi.org/10.4314/njt.v39i3.25